The simulations of sulfuric acid concentration and new particle formation in an urban atmosphere in China - Wang, Z. B.; Hu, M.; D. Mogensen; Yue, D. L.; Zheng, J.; Zhang, R. Y.; Y. Liu; Yuan, B.; Xin Li; Shao, M.; L. Zhou; Wu, Z. (Atmospheric Chemistry and Physics, 2013)
Simulations of sulfuric acid concentration and new particle formation are performed by using the zero-dimensional version of the model MALTE (Model to predict new Aerosol formation in the Lower TropospherE) and measurements from the Campaign of Air Quality Research in Beijing and Surrounding areas (CAREBeijing) in 2008. Chemical reactions from the Master Chemical Mechanism version 3.2 (MCM v3.2) are used in the model. High correlation (slope = 0.72, R = 0.74) between the modelled and observed sulfuric acid concentrations is found during daytime (06:00-18:00). The aerosol dynamics are simulated by the University of Helsinki Multicomponent Aerosol (UHMA) model including several nucleation mechanisms. The results indicate that the model is able to predict the on- and offset of new particle formation in an urban atmosphere in China. In addition, the number concentrations of newly formed particles in kinetic-type nucleation including homogenous homomolecular (J=K[H2SO4]2) and homogenous heteromolecular nucleation involving organic vapours (J=K-het[H2SO4][Org]) are in satisfactory agreement with the observations. However, the specific organic compounds that possibly participate in the nucleation process should be investigated in further studies. For the particle growth, only a small fraction of the oxidized total organics condense onto the particles in polluted environments. Meanwhile, the OH and O3 oxidation mechanism contribute 5.5% and 94.5% to the volume concentration of small particles, indicating the particle growth is more controlled by the precursor gases and their oxidation by O3.